Inovasi Pengolahan Kopi Jahe Celup sebagai Produk Unggulan untuk Pemberdayaan Ekonomi di Desa Sapit, Kecamatan Suela, Kabupaten Lombok Timur - Miptahul Rizki (Universitas Mataram, 2025)
Sapit Village, located in Suela Subdistrict, East Lombok Regency, holds significant potential in the agriculture and plantation sectors, particularly in coffee and ginger production. However, the lack of effective commodity management has limited market access for local communities. This research aims to develop innovative ginger coffee sachets as a flagship product to enhance the added value of local agricultural produce while empowering the village's economy. The study employs an experimental approach, focusing on processing Arabica coffee beans and ginger into the final product of ginger coffee sachets. The findings reveal that ginger coffee sachets have significant market potential due to their practicality and the health benefits associated with ginger. This innovation not only addresses the limitations of local commodity processing but also increases community income and creates new business opportunities